Realisation of one‐dimensional (Si/SiO2)N PC filter in visible light band. (1st December 2018) - Yang, Yibiao; You, Yi; Zhao, Xiaodan; Chen, Zhihui; Zhang, Mingda; Fei, Hongming
Abstract : The work proposes a one‐dimensional photonic crystal (PC) filter with (Si/SiO2 ) N structure, which is used to filter in the visible light band. The optical properties are simulated theoretically by using the transfer matrix method. Propagating properties under different incident angles and different period numbers for both Transverse Electric (TE) mode and Transverse Magnetic (TM) mode are studied. A photonic bandgap (PBG) is found between 450 and 700 nm. For both TE and TM modes, the blue shift can be found as the incident angle increases. The PC films are prepared by radio‐frequency (RF) magnetron sputtering experimentally. The experimental results are in accordance with the simulation results. The results indicate that the PBG is related to the incident angle and the period number, and increasing the period number is a feasible way to ensure the stability of the PBG. The studies are beneficial to the design of the PC filter in the future.